Socio-rhetorical re-examination of Luke 9:51–56: Mission, migration, and nationalism - Aryeh, Daniel N. A. (HTS teologiese studies, 2024)
The conjoined themes of mission, migration, and nationalism are central issues in the Gospel of Luke. These essential motifs were amalgamated in a rhetorical composition to persuade implied readers to be mission-focused but accommodate the views of transiting communities or consular decisions and national pride. Luke 9:51–56 has been variedly interpreted on discipleship, media communication, Christological, and Elijah’s spirit tenets. Emphasising individual themes in the interpretation of Luke 9:51–56 is legitimate, but it leaves out a holistic understanding of the text as the opening narrative of Luke’s travel narratives, which concerns multiple issues. This study engages the socio-rhetorical criticism propounded by Vernon K. Robbins to reinterpret Luke 9:51–56. The objective is to respond to the questions: (1) what is the relationship between mission, migration, and nationalism in Luke 9:51–56? and (2) what is the relevance of mission, migration, and nationalism in Luke 9:51–56 for African migrants in the diaspora?Contribution: There is a proximity between mission, migration, and nationalism in Luke 9:51–56. It prioritises mission over migration and nationalism. Mission is the key determinant for migration and nationalism. Migrant Africans emphasise migration for economic fortunes over mission and nationalism. This may be due to personal aspirations.